Palmeiras, the knowledge of experience in the popular movement - kelma Socorro Lopes de Matos (Universidade Federal de Santa Maria, 2012)
The present study was conducted in the following areas: the Union of Communities of the Great Fortaleza (UCGF), The Federation of Neighborhoods and Slums de Fortaleza (FBFF) - general entities popular organization, with leaders of neighborhoods Lagamar, Pirambu and Conjunto Palmeiras, The Secretariat Work and Social Action (interviews with technical and documentary research) were also consulted newspapers: Daily Northeast, the PEOPLE, and Tribune of Ceará (1960-1993), in addition to newsletters, newspapers and books of general entities and organizations neighborhoods. Events were recorded and general meetings of the bodies moving in Fortaleza, prioritizing the testimonies of the residents / social actors. It is essential to the "recovery of these experiments" to bunderstand the processes of growth, and the dynamics of everyday life this locus. In this study the Palms was nominated for a significant part of the leaders of the popular movement, as an example to be followed by its position, organization and performance differential. This characteristic of the strength of the politics of unity is also expressed in how the Association of Residents of Conjunto Palmeiras - ASMOCONP always acted: with transparency, seeking dialogue, democracy, and participation of residents, opting for solidarity as a growth target.